(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2018)
This chapter investigates the development of audiovisual media through the prism of popular music performance on television, as it developed in the rich music environment around and within the Danish Broadcasting Company (DBC) during the 1960s and 1970s. The focus is on the relation between the institutional setting and the preferred program formats’ visualization of music. On the one hand, music on television influenced the relationship between musical genres and visual (re)presentations, and helped to shape the (changing) visual genre conventions. On the other, generational discussions of music programming, choice of repertoire and not least how the various concert formats were (or were not) linked to a notion of liveness can be seen as a changing agent for the institutional approach to audiovisuality. The study draws on archival television program material and interviews with former employees from DCB, and discusses television concerts as the prevailing programming ideal for Danish television in the period 1964–1978.